Efforts to Improve Students' Mathematics Learning Outcomes through the Contextual Teaching and Learning (CTL) Learning Model on Cube and Block Materials in Class VIII A Christian Junior High School - Nolce Nolceana Elisabeth Edita (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
Abstract The background of this study is the low mathematics learning outcomes of grade VIII A students at SMP Kristen Kefamenanu in the topic of cubes and rectangular prisms. Students experienced difficulties in understanding problem-solving steps, used incorrect formulas, and had a limited undersanding of mathematical symbols. This indicates the need for a learning model that can help students connect the material to real-life experiences. The objective of this study is to improve student learning outcomes through the implementation of the Contextual Teachung And Learning (CTL) approach. This research is a classroom action research (CAR) conducted in two cycles involving 26 students as subjects. Data collection techniques included observations and learning outcome tests. The results showed an improvement in learning outcomes from cycle I, with a mastery level 57.69% and an average student activity score of 2,00 (categorized as low), to 80,76% in cycle II with an average activity score of 3.00 (categorized ad good). Thus, the implementation of the Contextual teaching and learning (CTL) learning model proved to be effective in improving students’ mathematics learning outcomes in the topic of cubes and rectangular prisms.